Implementasi Akad Murabahah dan Dampaknya Pada Produk Cicil Emas di Bank Syariah Indonesia (BSI) KCP Kediri Pare - Santoso, Auliya Elvansa; Sopingi, Imam; Yuni K, Kusnul Ciptanila (Program Studi Ekonomi Islam, Fakultas Ekonomi, Universitas Hasyim Asy'ari Tebuireng, 2025)
This study analyzes the implementation of the murabaha contract in the gold installment product at Bank Syariah Indonesia (BSI) KCP Kediri Pare and its impact on customers and banks. Using a qualitative approach, data were collected through in-depth interviews with customers and bank staff, direct observation, and analysis of operational documents. The results show that the murabahah contract on gold installments makes it easy for customers to own gold with a transparent installment system. In addition, this product increases customer loyalty and bank image. However, there are still obstacles in customer understanding of the contract mechanism, so further education is needed to reduce potential misunderstandings. The implication of this study is the importance of improving Islamic financial literacy to ensure that customers understand the sharia principles in their transactions, which in turn can strengthen the Islamic financial industry as a whole.